Single point positioning performance of single-frequency code-based mode with ionospheric modelling: a case study over Iran. Issue 3 (2nd September 2022) - Nobakht-Ersi, Fereydoun; Safari, Abdolreza
ABSTRACT: This contribution is aimed to show that careful ionospheric modelling can enhance the single-frequency code single point positioning (SPP) performance for both kinematic and static scenarios. Attention is restricted to the SPP quality driven by the IRIM under geomagnetic storm conditions. A Kalman filter-based model is formed for kinematic/static SPP users with which one combines GPS single-frequency code observations with the ionospheric corrections. To demonstrate the SPP quality, experimental datasets of the Iran permanent GPS network are analysed using self-developed software and Bernese5. It is shown how the IRIM improves the SPP performance as compared to the global KIM corrections.